Urban Renewal, Governance and Sustainable Development: More of the Same or New Paths? (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Rio Declaration of 1992 and its agenda for action in the twenty first century—Agenda 21—were bold attempts at steering the nations in the world in the direction of ecologically sustainable development, a direction including social and environmental justice on a global scale. It did not take long, however, when the meaning of the word ’sustainable’ became diluted, sometimes even in the direction of an empty 'sustainababble´. Thus, what we see today is a huge variety of more or less scholarly based ‘sustainability’ imaginaries stating what the major problems facing humanity are represented to be and how they should be acted upon by science, economy, politics, and in everyday life. In other words, 'sustainability' is not enough. To evade the impression that the word may simply encourage the sustaining of an unjust status quo and that everyone has common interests in 'sustainable urban development' research and policy practice have to unmask the real conflicts of interest hidden behind the use of slippery language.